Publicidad y globalización - Caro, Antonio (Historia y Comunicación Social, 2010)
The purpose of this paper is to analyze the role that advertising performs in the present capitalist globalization process, by means of highlighting how advertising has been established as the nucleus of a globalized imaginary that works as an ideological platform for the economic capitalist expansion. In this sense, the paper empathizes the fact that advertising works like the imaginary element that, once inserted into the culture of a lot of different societies which may even displace them, penetrate in local environment, settling down the basis for the capitalist economic expansion.